Report on the international scientific conference Relevance and listening: communicating the Christian message in the plurality of contemporary voices, organised by the Department of Institutional Social Communication of the Pontifical University of the Holy Cross, Rome, May 2-4, 2023 - Leśniczak, Rafał (Folia Toruniensia, 2023)
From 2 to 4 May 2023 an international scientific conference entitled “Relevance and listening: communicating the Christian message in the plurality of contemporary voices” was held in Rome. The meeting was organised by the Department of Institutional Social Communication of the Pontifical University of the Holy Cross in Rome. The aim of the conference was to analyse the challenges related to the proper understanding and implementation of institutional communication processes of ecclesiastical institutions in the perspective of the contemporary socio-political and cultural context. The conference’s main speakers were, among others, Prof. Jim Macnamara (University of Technology of Sydney), Prof. José María La Porte (Pontificia Università della Santa Croce), Prof. Benedetto Ippolito (Università Roma Tre) and Prof. Lorenzo Cantoni (Università della Svizzera Italiana).